2016
DOI: 10.4081/ejh.2016.2638
|View full text |Cite
|
Sign up to set email alerts
|

The Bromodomain testis-specific gene (Brdt) characterization and expression in gilthead seabream, Sparus aurata, and European seabass, Dicentrarchus labrax

Abstract: Multiple genes and transcription factors are involved in regulation and control of the complex process of sex determination and differentiation of fish species. Also more, several hormonal factors and some environmental conditions can also be adequate spawning strategies and stimuli for inducing reproduction of fish species. Brdt gene belongs to the bromodomain-extraterminal domain (BET) family of transcriptional coregulators. In mammals, Brdt gene is almost exclusively expressed in testis. Furthermore, Brdt p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The inter-and intra-specific differences indicated in BRDT expression levels in different species of fish (including zebrafish in the present study; i.e. higher levels of BRDT in the ovaries than in the testes) suggest a different role of BRDT protein during both spermatogenesis and oogenesis, as a transcriptional regulator and/or for chromatin remodeling and compaction depending on the species, as reported in mammals and fish (Taniguchi 2016, Úbeda-Manzanaro et al 2016. In the present study, in the zebrafish testes, basal expression levels of BRDT transcripts increased significantly with exposure to daidzein (at 10 mg l −1 ), but not with exposure to the same dose of genistein.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…The inter-and intra-specific differences indicated in BRDT expression levels in different species of fish (including zebrafish in the present study; i.e. higher levels of BRDT in the ovaries than in the testes) suggest a different role of BRDT protein during both spermatogenesis and oogenesis, as a transcriptional regulator and/or for chromatin remodeling and compaction depending on the species, as reported in mammals and fish (Taniguchi 2016, Úbeda-Manzanaro et al 2016. In the present study, in the zebrafish testes, basal expression levels of BRDT transcripts increased significantly with exposure to daidzein (at 10 mg l −1 ), but not with exposure to the same dose of genistein.…”
Section: Discussionsupporting
confidence: 72%
“…Most genes involved in reproduction, hatching, development and epigenetic processes (e.g. oestrogens and receptors, choriogenins, HEs, apoptotic and epigenetic markers, bromodomains) express constitutively at high or moderate levels in the gonads and during the early stages of development and life, as has been reported in different species of fish including zebrafish (Segner et al 2003, Chandrasekar et al 2010, Úbeda-Manzanaro et al 2016, Sarasquete et al 2018a, González-Rojo et al 2019. All these findings corroborate the maternal origin of mRNA transcripts and their transfer to the progeny, since the oocyte is the starting point of a new generation.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The results of previous immunofluorescent and ultrastructural analyses showed that blocking the removal of histones, during the exchange of these proteins into protamines, hindered the proper course of spermiogenesis [3,28]. The studies of spermatogenesis concerning Brdt gene in two fish species, which have different methods of nuclear protein exchange, revealed variations in this gene expression which could indicate a different role of Brdt protein [29]. The exchange of nucleoproteins in one of these species (Dicentrarchus labrax) follows the same scheme as in Chara [30].…”
Section: Introductionmentioning
confidence: 99%